2016
DOI: 10.1038/srep36618
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations by indoxyl sulfate in skeletal muscle induce uremic sarcopenia in chronic kidney disease

Abstract: Sarcopenia is associated with increased morbidity and mortality in chronic kidney disease (CKD). Pathogenic mechanism of skeletal muscle loss in CKD, which is defined as uremic sarcopenia, remains unclear. We found that causative pathological mechanism of uremic sarcopenia is metabolic alterations by uremic toxin indoxyl sulfate. Imaging mass spectrometry revealed indoxyl sulfate accumulated in muscle tissue of a mouse model of CKD. Comprehensive metabolomics revealed that indoxyl sulfate induces metabolic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 48 publications
(55 reference statements)
5
157
1
3
Order By: Relevance
“…Recently, Sato et al also demonstrated that IS potentiated mitochondrial dysfunction as well as our study. In addition, a significant inverse association between plasma IS levels and skeletal muscle mass in patients with CKD was observed 44. The data suggest that IS is a pathogenic factor for muscle atrophy in the patients with CKD.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, Sato et al also demonstrated that IS potentiated mitochondrial dysfunction as well as our study. In addition, a significant inverse association between plasma IS levels and skeletal muscle mass in patients with CKD was observed 44. The data suggest that IS is a pathogenic factor for muscle atrophy in the patients with CKD.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, a significant inverse association between plasma IS levels and skeletal muscle mass in patients with CKD was observed. 44 The data suggest that IS is a pathogenic factor for muscle atrophy in the patients with CKD. However, the clinical data reported by Sato et al were a correlation study and, as a result, would not have the same relevance as would be obtained in a large randomized study.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings revealed that microbiota metabolism is completely responsible for the accumulation of indoxyl sulfate and p-cresyl sulfate, which are the major uremic toxins involved in the progression of CKD, cardiovascular disease, and muscle loss. 6,27 Additionally, of the M-USs, TMAO increases the risk of cardiovascular disease via its potent proatherosclerotic and prothrombotic effects. 28 Dimethylglycine has also been associated with an increased risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings implicate LPS and inflammation as causative agents in the process, inflammation-independent alterations in skeletal muscle metabolism have also been observed. For example, in response to the gut microbiota-specific metabolite indoxyl sulfate [38], C2C12 myoblasts exhibit an up-regulation of glycolysis and an increase in the activity of the pentose phosphate pathway [39]. Similarly, exposure of myotubes to gut microbial-derived extracellular vesicles induces insulin resistance [30], highlighting the multitude of ways in which gut microbiota may influence the metabolic function of skeletal muscle.…”
Section: Gut Microbiota and Skeletal Muscle Metabolismmentioning
confidence: 99%